Food Citizenship and Governmentality: Neo-Communitarian Food Governance in The Hague - Jhagroe, Shivant (2019)
This article presents an account of food citizenship based on a governmentality framework. Moving beyond the dichotomy of democratic or neoliberal accounts of food citizenship, a food governmentality framework is presented. This Foucaultian inspired framework conceptualises food citizenship as identity formation in relation to various modes of power that govern food systems and subjects in significantly different ways. The article empirically illustrates how food citizenship relates to food governmentality by focussing on the food-related activities of a Transition Town initiative in the Netherlands (The Hague) called Den Haag In Transitie (DHIT). By defining food as a community issue, and employing holistic-spiritual and collaborative knowledge, food citizens in the DHIT case render sustainable food systems governable in radically new ways. I argue that this type of citizenship can be considered neo-communitarian food citizenship and moves beyond democratic or neoliberal accounts. Finally, the article reflects on neo-communitarian citizenship and argues for a nuanced understanding of food citizenship, moving away from either democratic romanticism or neoliberal criticism.